COMPLIANCE OF HOUSING DEVELOPMENT LIMITED LIABILITY COMPANIES WITH DETAILED SPATIAL PLANNING IN THE LAND MATURITY STAGE - Andry Kosasih; Kamaluddin; Khairunnisah; Irman Syahriar (Awang Long Law Review, 2026)
This study examines the compliance of limited liability companies developing housing with the Detailed Spatial Planning (RDTR) at the land preparation stage within the framework of the risk-based business licensing regime following the Job Creation Law and Government Regulation 5/2021 and its updates through Government Regulation 28/2025. The RDTR is positioned as a central legal instrument and a tool for testing the material legality of spatial utilization, so that land preparation activities such as cut and fill, land clearing, and backfilling must be in line with established zoning and spatial function provisions. The research findings indicate that the risk-based licensing system through the OSS encourages formal document-based compliance (NIB, KKPR/PKKPR, and other basic requirements) rather than substantive compliance with physical actions in the field, resulting in a gap between administrative legality and material legality. By using normative legal research methods and analytical tools of Lawrence M. Friedman's Legal System Theory, Soerjono Soekanto's Legal Effectiveness Theory, Legal Compliance Theory, and Legal Protection Theory, this study found that compliance weaknesses stem from the disharmony between the orientation of accelerated investment and the demands of spatial planning prudence, the suboptimal integration of RDTR and spatial data in the OSS, and weak substantive supervision and compliance culture among developers. The study recommends strengthening the integration of RDTR in the OSS system, improving the quality of RDTR and spatial data infrastructure, enforcing consistent supervision and sanctions from the land preparation stage, and fostering a substantive compliance culture within the developer corporation environment so that the goals of sustainable spatial planning and protecting the interests of the community can be achieved more effectively.